Adherence to therapy enhanced by a pharmaceutical service: dose administration aids - Ribeiro, Margarida Lopes de Pina (2021)
The average life expectancy has been increasing due to aspects such as the advances in medicine and technology. An older population leads to the appearance of several chronic pathologies regarding polymedication, and the outcomes highly depend on patients’ adherence to treatment. This is one of the most determining factors in cure, stabilization, or regression of the disease. The purpose of this project is to highlight the principal failures in the patient journey, from medical appointment to the treatment itself, and to analyze the pharmacist’s role as an adherence promoter. In order to understand the gaps, interviews were made to the three main actors in the patient journey (physician, pharmacist, and patient). This study supports the implementation of a new service in a local community pharmacy of Abrantes. Throughout the interviews it was possible to infer the main adherence to therapy failures, such as the lack of cooperation between healthcare professionals, a non-existent patient-oriented follow-up, and a communication gap between the three main groups. This project also aimed to overcome the obstacles in the patient journey and to increase adherence to therapy by launching a medication management service for patients – Dose Administration Aids (DAA). Thus, to understand the service's feasibility, it was observed the implementation of DAA in a community pharmacy in Abrantes. Despite claiming some requirements, it was possible to conclude the service benefits both customers and pharmacy.